Entre activistes et fonctionnaires : le mouvement Cultura Viva Comunitaria et les politiques culturelles à La Paz et El Alto - Baptiste Mongis (IdeAs)
In Bolivia, the autonomous city of La Paz, through the "Law of Cultures" promulgated in 2017, has a program to support art and culture, FOCUART, while the neighboring city of El Alto, for its part, attempted in 2019 to put in place its own legislation in this area. Both of these initiatives included a "community living culture" component. This formula is in line with the dynamics driven by the Cultura Viva Comunitaria movement, whose first congress was held in 2013 in La Paz, and which has asserted itself at the regional level by involving community cultural organizations, states and municipalities in a relationship that is sometimes complicit, sometimes tense, and sometimes marked by mutual indifference. Through these two case studies, we propose to analyze some of the interactions that take place between institutional actors and activists in the development of cultural policies in their cities.